Inferior outcomes with reduced intensity conditioning followed by allogeneic hematopoietic cell transplantation in fit individuals with acute lymphoblastic leukemia: a Canadian single-center study and a comparison to registry data. Issue 9 (29th July 2021) - Pasic, Ivan; Paulson, Kristjan; Dozois, Graham; Schultz, Kirk R.; Lipton, Jeffrey H.; Kumar, Rajat
Abstract: Allogeneic hematopoietic cell transplantation (HCT) can offer cure to some patients with acute lymphoblastic leukemia (ALL). It remains unclear how conditioning intensity affects transplant outcomes in ALL. In this retrospective study, we compared outcomes between 27 patients <60 who received reduced intensity conditioning (RIC) at Princess Margaret Hospital Cancer Center (PMCC) and 226 Cell Therapy Transplant Canada (CTTC) age-matched controls who received myeloablative conditioning (MAC) between 2007 and 2018. Compared to CTTC patients, PMCC patients had an inferior 2-y OS: 0.29 (95% CI: 0.11–0.49) vs 0.63 (0.56–0.70), HR = 2.10 (1.23–3.55), p =  0.006, higher TRM: 0.41 (0.22–0.60) vs 0.24 (0.18–0.30), HR = 2.00 (1.05–3.81), p =  0.04 and a trend toward increased risk of relapse: 0.36 (0.17–0.56) versus 0.17 (0.12–0.22), HR = 1.72 (0.82–3.62), p =  0.15. In multivariate analysis, RIC and the use of T-cell depletion (TCD) were associated with inferior OS. In ALL patients <60, the use of RIC with TCD is associated with inferior allogeneic HCT outcomes.